Browning Index of Anthocyanin‐Rich Fruit Juice Depends on pH and Anthocyanin Loss More Than the Gain of Soluble Polymeric Pigments. Issue 4 (25th March 2018) - Dorris, Matthew R.; Voss, Danielle M.; Bollom, Mark A.; Krawiec‐Thayer, Mitchell P.; Bolling, Bradley W.
Abstract : Abstract: Browning index (BI, ABS520 nm /ABS420 nm ) is a measure of anthocyanin‐rich fruit juice pigmentation quality. This study sought to determine the extent to which BI describes anthocyanin quality and degradation in fruit juices. Commercial fruit juices were assayed for monomeric anthocyanin (MA) content, percent polymeric color (%PC), pH, and BI. BI varied, 0.29 to 1.72, among cranberry, cherry, grape, aronia, and pomegranate juices. Principal component analysis (PCA) revealed that BI was strongly inversely associated with %PC, and positively correlated with MAs to a lesser extent. The BI of grape and cherry juices varied linearly with pH from 2.0 to 4.0 in pH‐adjusted juices. Cherry and grape juices at pH approximately 2.0 to 4.0 were incubated at 50 °C to induce juice browning. BI and MA decreased, and %PC increased, but the amount of MA degradation was not explained by %PC. In the aged juices, BI and MA were strongly correlated using PCA. In aged grape juice, chromatographic analysis was used characterize anthocyanins, proanthocyanidins, and anthocyanin scission products. Anthocyanin loss and a gain of unresolved components absorbing at 420 nm decreased BI. Proanthocyanidins and co‐eluting pigments with varying BI decreased during aging. Scission products did not account for anthocyanin loss. Thus, MA loss more so than the gain in pigments associated with juice proanthocyanidins contribute to the increase in %PC and decline of the BI during accelerated aging of grape juice. Thus, BI is a useful marker of fruit juice quality within juices of the same pH and anthocyanin composition. Practical Application: Fruit juice pigmentation depends on anthocyanins, pH, and other matrix components. Spectrophotometric methods to determine pigmentation include the browning index (ABS520 nm /ABS420 nm ), pH differential method for monomeric anthocyanin (MA) content, and bisulfite bleaching to determine percent polymeric color (%PC). In this study, anthocyanin‐rich fruit juice browning index was strongly dependent on pH and MA content. MA loss, and to a lesser extent, a gain in newly‐formed pigments at 420 nm contributed to the browning index change during aging. Therefore, browning index is strongly associated with MA content and is useful for assessing fruit juice quality.